Indonesia's Accountability as a State That Did Not Ratify the 1951 Refugee Convention on the Rohingya Ethnic Group in the Perspective of International Human Rights - Ahmad Lukman Hadi; Kholifatul Muna; Fanisa Mayda Ayiliani (Universitas Negeri Semarang, 2024)
of Rohingya ethnic refugees who come to Indonesia where Indonesia has not ratified the 1951 Refugee Convention so that it poses its own challenges in dealing with Rohingya refugees, so human rights aspects and various moral and empathetic efforts are still needed. The study uses a normative legal approach to analyze legal frameworks relevant to the Rohingya ethnic situation, highlighting the human rights protections provided by international legal instruments such as the UN Universal Declaration of Human Rights. The ongoing conflict in Myanmar shows the allegations/assumptions of systematic human rights violations, showing the need for joint action in upholding human rights principles. Although Indonesia has not ratified the 1951 Refugee Convention, the state has a moral and legal obligation to respect human rights, including in addressing the problem of the arrival of the Rohingya in terms of seeking asylum and shelter. The protection of refugees, including the Rohingya, is a fundamental moral and legal responsibility of the international community, which includes the Indonesian government. The Indonesian government has also taken steps to provide protection to refugees, including working with UNHCR in finding solutions for Rohingya refugees in Aceh. In the absence of Indonesia ratifying the refugee convention, moral and legal efforts are still needed to ensure proper protection for Rohingya refugees and uphold human rights principles at the international level.